Decoding Language Style Utilized by Men and Women on Instagram - Al-Munawarah, Afiah Lutfiah; Nirwana (Elite : English and Literature Journal, 2023)
This research aimed to find out the language style used by men and woman influencers on Instagram. The method that was used in this research was the descriptive qualitative method. The researcher collected the data from the captions on six (3 women and 3 men) selected Instagram accounts; some of the influencers are from the same backgrounds. The data were analyzed based on the theory proposed by Leech who stated that there are four general headings of language style: lexical categories, grammatical categories, figures of speech, and context and cohesion. The result of this study showed that, in the lexical categories, men and women use all kinds of nouns, verbs, adjectives, and adverbs based on the objective of the captions. The researcher discovered a wide variety of sentence patterns in the grammatical categories through the captions, including declarative, command, exclamation, question, and minor sentences. The researcher discovered three different types of phrases namely: noun phrases, verb phrases, and adjective phrases. Both men and women use the figure of speech features in their Instagram captions. Related to context and cohesion, interpersonal and situational information is employed in their captions. Additionally, the researcher primarily discovered reference kinds despite the fact that both men and women employed all forms of cohesiveness.